Asymmetric motives in Indian bilateral cross-border joint ventures with G7 nations: impact of relative partner characteristics and initial conditions. (1st January 2013) - Dhir, Sanjay; Mital, Amita
The determinants of asymmetric motives of partners in cross-border joint ventures (CBJV) have not been adequately explored in the context of developing nations. Though there are several empirical studies for motives of partners in CBJV in developed nations but, there is no systematic empirical evidence for the same in developing nations. Another lacuna is regarding studies which analyse antecedents to these asymmetries. This article analyses relative partner characteristics and initial CBJV conditions as antecedents to the degree of asymmetric motives between CBJV partner firms in developing nation. An empirical analysis of 201 bilateral CBJVs in India with G7 nations, for a time period of ten years (2000–2010), shows that while degree of asymmetric motives between partners firms enhances when relative culture difference, capital structure and inter-partner product-market overlap increases, higher level of diversification, critical activity alignment and resource heterogeneity decreases the degree of asymmetric motives between partner firms in CBJV.